2006
DOI: 10.1007/s10072-006-0579-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of aura: solving the puzzle

Abstract: Migraine with aura (MwA) sufferers, at times, need specific treatments. This is the case when the auras are frequent, prolonged and cause anxiety and distress. Abnormal release of glutamate, which may trigger auras, and abnormal platelet behaviour, which constitutes a possible predisposing factor to MwA, are possible targets for MwA-specific prophylactic therapy. Here we present results obtained using lamotrigine (two open trials), an agent known to inhibit glutamate release, and picotamide, an antiplatelet dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…Lamotrigine is an antiepileptic drug acting by blocking voltage-sensitive channels leading to an inhibition of glutamate release [19]. A number of studies have confirmed the efficacy of lamotrigine in the prevention of the auras [20][21][22][23][24].…”
Section: Glutamate and Auramentioning
confidence: 99%
“…Lamotrigine is an antiepileptic drug acting by blocking voltage-sensitive channels leading to an inhibition of glutamate release [19]. A number of studies have confirmed the efficacy of lamotrigine in the prevention of the auras [20][21][22][23][24].…”
Section: Glutamate and Auramentioning
confidence: 99%
“…If we speculate that a similar alteration is present in migraine, we could hypothesize that an abnormal release of glutamate in the intersynaptic space, leading to an increased excitability of the cerebral cortex with development of the spreading depression, may induce an increase of plasma concentrations of the amino acid, and consequently of platelet re-uptake. Strong support for this hypothesis is provided by the fact that lamotrigine, which inhibits glutamate release, reduces the frequency of MA attacks (25). This evidence, coupled with our data, may allow one to hypothesize that glutamate released from platelets plays an important role in the pathophysiology of MA and, based on this assumption, that glutamate release from activated platelets is also blocked by lamotrigine.…”
Section: Discussionmentioning
confidence: 99%
“…Stronger platelet aggregation with higher plasma serotonin levels provokes vasoconstriction [113]. In addition to platelet-released glutamate [54,114], a high serotonin concentration may induce gap-junctional slow calcium waves in astrocyte syncytium [115,116], thus being responsible for the slowly proceeding aura signs [117,118]. Platelet aggregation may be initiated by triggers that further enhance an already elevated platelet aggregability [119], such as emotional and physical stress, awakening in the morning, additives in food and beverages, oral contraceptives, and the monthly decrease of estrogen during the menstrual cycle [110].…”
Section: Arguments Against the Role Of Csd In Migraine Headachementioning
confidence: 99%